2023
DOI: 10.1002/ece3.9852
|View full text |Cite
|
Sign up to set email alerts
|

Nest building in titmice Paridae: Selectivity in bryophyte use

Abstract: Most birds build a nest for reproduction, and its basic function is to protect the eggs, chicks, and incubating and brooding parent (Hansell, 2000). Nests may provide an optimal microclimate, reducing heat loss, and protecting the contents from predators, ectoparasites,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 90 publications
1
0
1
Order By: Relevance
“…Nineteen species were recorded for Myadestes ralloides and seventeen for Catharus fuscater (Table 1). The number of bryophytes cited in our study (25 species) is higher than the 22 species [4], 7 species [6], and 15 species [27] reported in previous studies. Supporting our results, Calvelo et al [4] have shown that mosses and liverwort are the dominant components in nest construction.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…Nineteen species were recorded for Myadestes ralloides and seventeen for Catharus fuscater (Table 1). The number of bryophytes cited in our study (25 species) is higher than the 22 species [4], 7 species [6], and 15 species [27] reported in previous studies. Supporting our results, Calvelo et al [4] have shown that mosses and liverwort are the dominant components in nest construction.…”
Section: Resultscontrasting
confidence: 75%
“…The most frequent species in the nests of the two species were the mosses Thuidium tomentosum, Meteoridium remotifolium, Porotrichum mutabile, and Squamidium nigricans. In accordance, in a study conducted by Rydgren et al [27], it was found that there are 15 species of mosses (e.g., Pleurozium schreberi (Willd. ex Brid.)…”
Section: Resultssupporting
confidence: 71%